Analisis Kebutuhan Jagung Untuk Pakan Ternak Unggas di Sumatera Barat - Harmen Harmen (Jurnal Pembangunan Nagari, 2021)
Corn is the primary source of feed for poultry, with the composition in feed reaching 58%. The population and type of poultry largely determine the level of demand for corn. An analysis has been carrying out to determine the production and demand for corn per year. The amount of output must be increasing to meet the needs of poultry feed in West Sumatera. The study used secondary data from the Central Statistics Agency (BPS) of West Sumatra in 2020. The study used a quantitative descriptive method. The observations did in all districts/cities in West Sumatra, namely, the type and population of poultry, production per district, and the need for corn as poultry feed. The data were analyzed using excel for Windows and displayed in the form of images and tables. Analysis results show that the average annual demand for corn in West Sumatra for poultry feed is 3,774.1 tons/day, equivalent to 1,377,546.5 tons/year. The yearly average corn production is only 925,564 tons. Based on the analysis of needs and production, corn is not sufficient for poultry feed needs. It is necessary to increase corn production for poultry feed in West Sumatera by 0.48 million tons/year.